2019
DOI: 10.13189/ujer.2019.070925
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of School Based Management, and Its Effect on the Teachers' Work Motivation and the School Quality

Abstract: The three main purposes of the study were: (1) to describe the implementation of the school-based management, (2) to know the effect of the implementation of the school-based management on the teachers' work motivation, and (3) to know the effect of the school-based management on the school quality. The study was conducted in East Java, and the samples of the study were 87, which were taken by using area cluster random sampling technique. The data was collected by using questionnaire and then was analyzed by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 1 publication
2
4
0
6
Order By: Relevance
“…The results of this study are also in line with Wiyono's (2018) research which shows that the school principal's transformational leadership affects teacher work motivation and work effectiveness. The results of this study are also following the results of research by Bafadal et al (2019) which show that the quality of school-based management affects teacher work motivation and school quality. The higher the quality of school principal management, the higher the teacher's work motivation in carrying out tasks, and the higher the quality of education in schools.…”
Section: Hypothesis Testsupporting
confidence: 76%
“…The results of this study are also in line with Wiyono's (2018) research which shows that the school principal's transformational leadership affects teacher work motivation and work effectiveness. The results of this study are also following the results of research by Bafadal et al (2019) which show that the quality of school-based management affects teacher work motivation and school quality. The higher the quality of school principal management, the higher the teacher's work motivation in carrying out tasks, and the higher the quality of education in schools.…”
Section: Hypothesis Testsupporting
confidence: 76%
“…Moreover, the work environment and the teacher innovation are largely determined by the management and leadership of the principal. In addition, many other research results showed that the quality of school management affects teachers' work motivation and the quality of education in schools directly (Bafadal et al, 2019;Wiyono, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Mencermati temuan penelitian di atas maka penerapan manajemen berbasis sekolah akan efektif dan memberikan keunggulan terhadap prestasi sekolah jika dilaksanakan oleh semua unsur yang terlibat baik kepala sekolah, komite sekolah dan lainya. Hal itu sesuai denga apa yang di sampaikan (Bafadal et al, 2019;Yulianti, 2020;H. A. Yusuf et al, 2019) bahwa manajemen berbasis sekolah, kepemimpinan berbasis sekolah, serta manajemen dan kepemimpinan memiliki efek positif pada prestasi sekolah.…”
Section: Gambar 3 Konstelasi Desain Managemen Scientific Learning Programs Dalam Proses Pembelajaranunclassified